Diffusion at interfaces: microscopic concepts: proceedings of a workshop Campobello Island, Canada, August 18 - 22, 1987 - Grunze, Michael; Kreuzer, H. J.; Weimer, J. J. (Springer, 1988)
Diffusion in solids and at interfaces is a very active area of research, as the contributions to this volume attest
Keywords: Konferenzschrift -- 1987 -- Campobello Island; Diffusion; Festkörperoberfläche